Prognostic Impact of PCK1 Protein Kinase Activity-Dependent Nuclear SREBP1 Activation in Non-Small-Cell Lung Carcinoma - Shao, Fei; Bian, Xueli; Wang, Juhong; Xu, Daqian; Guo, Wei; Jiang, Hongfei; Zhao, Gaoxiang; Zhu, Lei; Wang, Shuai; Xing, Dongming; Gao, Yibo; He, Jie; et al. (Frontiers in Oncology, 2021)
Metabolic enzymes can perform non-metabolic functions and play critical roles in the regulation of a variety of important cellular activities. Phosphoenolpyruvate carboxykinase 1 (PCK1), a gluconeogenesis enzyme, was recently identified as an AKT-regulated protein kinase that phosphorylates INSIG1/2 to promote nuclear SREBP1-dependent lipogenesis. However, the relationship of this regulation with the progression of non-small-cell lung carcinoma (NSCLC) is unclear. Here, we demonstrate that epidermal growth factor receptor (EGFR) activation induces AKT-dependent PCK1 pS90, PCK1-mediated INSIG1 pS207/INSIG2 pS151, and nuclear SREBP1 accumulation in NSCLC cells. In addition, the expression levels of AKT pS473, PCK1 pS90, INSIG1 pS207/INSIG2 pS151, and nuclear SREBP1 are higher in 451 analyzed human NSCLC specimens than in their adjacent normal tissues and positively correlated with each other in the tumor specimens. Furthermore, the expression levels of PCK1 pS90, INSIG1 pS207/INSIG2 pS151, and nuclear SREBP1 are associated with TNM stage and progression in NSCLC. Importantly, levels of PCK1 pS90 or INSIG1 pS207/INSIG2 pS151 are positively correlated with poor prognosis in NSCLC patients, and the combined expression value of the PCK1 and INSIG1/2 phosphorylation has a better prognostic value than that of each individual protein phosphorylation value and is an independent prognostic marker for NSCLC. These findings reveal the role of PCK1-mediated nuclear SREBP1 activation in NSCLC progression and highlight the potential to target the protein kinase activity of PCK1 for the diagnosis and treatment of human NSCLC.